The experience of perennial growing up of fingerlings of noble crayfish Astacus astacus for aquaculture needs - Golubev, Alexander P.; Alekhnovich, Anatoly V.; Bodilovskaya, Olga A.; Ulashchyk, Ekaterina A.; Gopinathan, Anilkumar (Journal of the Belarusian State University. Ecology, 2022)
The method of accelerated artificial rearing in aquaculture of Astacus astacus fingerlings in climatic conditions of Belarus has been elaborated. Initially, newborn A. astacus larvae were reared from early July to early October (summer period) in open-air trays at temperatures 12-25 °C. In successive winter period (early October - early April) grown up individuals were reared in aquaria in a heated room at temperatures 18-20 °C. The average weight of specimen at the end of summer period decreased from 392 to 265 mg with the increase of final stocking density from 6 to 54 ind/m-2. The average weight of individuals at the end of winter rearing changed irregularly from 688 mg to 939 mg within the final density gradient 58-122 ind/m-2. It is close to similar data for juveniles in natural reservoirs at the end of the first and second summer of their life. The equation between geometric mean (N, ind/m-2) of density on the whole period of rearing and average body weight (W, mg) for individuals aged 3.5-4 months calculated from the results of present investigations and the relevant literature data as follows: W = 424-1034gN. A similar equation for individuals aged 9-10 months after winter rearing is follows: W= 1376-278-lgN. These equations provide an alternative in aquaculture strategy to produce more juveniles with lower body weight or fewer larger ones. Generally, the introduction of 9-month-old A. astacus into ponds makes it possible to obtain specimens of marketable weight ( 10 g) in Belarus at the age of two years, or one-two years earlier than those in natural reservoirs. The maximal initial density (No) of rearing in aquaculture of newborn larvae A. astacus and specimen at the age Nu 3-4 months can be calculated according to the equation: No= -7^, where Nlim is the density of individuals at the end of period of rearing calculated from the above equations at which their weight will correspond to those for individuals in natural reservoirs at the end of their first or second summer of their life; S - survival of individuals in aquaculture expressed in fraction of unity. According to this equation, No for the first and second age groups are 423 and 33 ind/m-2 respectively.